2011
DOI: 10.1002/app.34071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solvent mixture on the properties of solvent cast polylactic acid (PLA) film

Abstract: The objective of this study was to investigate the effects of various solvents on the crystallinity and thermal expansion stability of PLA film. Three different PLA films were produced by the solvent casting technique; PLA in chloroform (PLA-C), PLA in methylene chloride (PLA-M), and PLA in methylene chloride: acetonitrile ¼ 50: 50 (PLA-MA). The PLA-MA had higher % crystallinity, 46.15, than the PLA-C, 24.03, and the PLA-M, 14.25. With this increase in crystallinity, the PLA-MA had improved thermal expansion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…The averaged complex and storage moduli was over 960 MPa with a standard deviation [18]. The influence of the solvent on polymer films' mechanical properties has been reported for such thermoplastics as PLA [34] and polystyrene [35]; therefore, this may also be the case for PIM-1. It is also necessary to consider the influence of polymer treatment on the results, as polymers are susceptible to processing history and every step, from polymer preparation in granular form to diluting it in different solvents, casting and drying in different conditions, may be significant to a final outcome.…”
Section: Dynamical Mechanical Thermal Analysismentioning
confidence: 76%
“…The averaged complex and storage moduli was over 960 MPa with a standard deviation [18]. The influence of the solvent on polymer films' mechanical properties has been reported for such thermoplastics as PLA [34] and polystyrene [35]; therefore, this may also be the case for PIM-1. It is also necessary to consider the influence of polymer treatment on the results, as polymers are susceptible to processing history and every step, from polymer preparation in granular form to diluting it in different solvents, casting and drying in different conditions, may be significant to a final outcome.…”
Section: Dynamical Mechanical Thermal Analysismentioning
confidence: 76%
“…It should be noted that a crystallization double peak for PLA has been observed during the heating cycle in experiments carried out by Liao et al [25] but no similar observations have been reported for crystallization from the melt state. In studies of the crystallization behaviour of PLA solvent-cast films Byun et al [26] have found that the formation of a single or double melting peak depends on the nature of the solvent, which determine whether mostly the PLA α-phase is formed or whether a mixture of α, β and γ crystals.…”
Section: Observations Of Events During Cooling From the Melt And Heatmentioning
confidence: 99%
“…PLA films containing OTM presented practically no drastic variation of T m . Furthermore, T m values of the PLA films either non‐plasticized or plasticized by OTM are higher than those presented by PLA pellet, which is related to the fact that chloroform tends to increase the crystalline perfection due to its interaction with the polymer …”
Section: Resultsmentioning
confidence: 83%
“…However, PLA/OTM films presented three crystalline reflections at 17, 19, and 23° indicating that these films are semi‐crystalline materials. According to Byun et al these reflections are characteristics of PLA casting films from chloroform. It is interesting to note that the intensity of the reflection at 23° increases as OTM content increases from 1 to 5 wt%, but it is not significant when the content increases from 5 to 10 wt% OTM.…”
Section: Resultsmentioning
confidence: 99%